To Leslie - Binaco, Ryan; Damon, Buck (A contracorriente films, 2023)
Inspired by true events. A West Texas single mother wins the lottery and squanders it just as fast, leaving behind a world of heartbreak. Years later, with her charm running out and nowhere to go, she fights to rebuild her life and find redemption.--IMDb
Orig.: USA, 2022
Keywords: Alleinerziehende Mutter; Mutterrolle; Melodrama; Spielfilm; USA; Single mothers / Drama; Mothers and sons / Drama; Life / Drama; Women / Drama; Feature films; Film; DVD-Video